2018
DOI: 10.4028/www.scientific.net/msf.921.111
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Investigation of Tm<sup>3+</sup>- Doped Li<sub>3</sub>Gd<sub>3</sub>Te<sub>2</sub>O<sub>12</sub> Blue-Emitting Phosphor

Abstract: A novel blue-emitting phosphor, Li3Gd3Te2O12:Tm3+ for white light-emitting diodes (W-LEDs) was prepared by solid-state synthesis and its structure and luminescence properties were investigated. This phosphor shows a satisfactory blue performance (peak at 458 nm) due to the 1D2 → 3F4 transition of Tm3+ excited by 361 nm light. Investigation of Tm3+ content dependent emission spectra indicates that x = 0.03 is the optimum doping content of Tm3+ ions in the Li3Gd3Te2O12 host. The critical distance and the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…3 curve (b) displays the emission spectrum of Ca2MgTeO6:0.02Tm3+ at near-UV light λex = 359 nm. The main emission band at 457 nm due to the electronic dipole transition of 1D2 →3F4 of Tm3+ [15]. Importantly, the blue region's emission peaks suggested that Ca2MgTeO6:Tm3+ can be promising blue-emitting phosphors.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…3 curve (b) displays the emission spectrum of Ca2MgTeO6:0.02Tm3+ at near-UV light λex = 359 nm. The main emission band at 457 nm due to the electronic dipole transition of 1D2 →3F4 of Tm3+ [15]. Importantly, the blue region's emission peaks suggested that Ca2MgTeO6:Tm3+ can be promising blue-emitting phosphors.…”
Section: Resultsmentioning
confidence: 98%
“…Rare-earth ions doped tellurates have arisen extensive interest due to excellent chemical and physical stability, such as Li3Gd3Te2O12:Dy 3+ , Ca3TeO6:Eu 3+ , and NaLaCaTeO6:Mn 4+ [10][11][12][13]. Tm 3+ is widely used as an efficient blue light emitting center , such as CaHfO3:Tm 3+ , Li3Gd3Te2O12:Tm 3+ , Ca9NaGd2/3(PO4)7:Tm 3+ , and CaBi4Ti4O15:Tm 3+ ,Yb 3+ many alternative Tm 3+ -doped phosphors have been reported [14][15][16][17]. Ca2MgTeO6 ceramics were reported to a double perovskite family member and exhibited a monoclinic P21/n structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…As is well-known, rare-earth ions doped tantalates have arisen extensive interest due to excellent [12][13][14][15][16][17]. In this work, Tm 3+ -doped SrBi 2 Ta 2 O 9 blue-emitting phosphor for W-LEDs has been synthesized at 1200 °C in an ambient atmosphere by solidstate reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Tm 3+ is widely used as an efficient blue light emitting center [13]. CaHfO3:Tm 3+ , Li3Gd3Te2O12:Tm 3+ , and CaBi4Ti4O15:Tm 3+ ,Yb 3+ , etc., many alternative Tm 3+doped phosphors have been reported [14][15][16]. In this work, Tm 3+ -doped Ba2Y3(SiO4)3F blue-emitting phosphor for W-LEDs has been synthesized by solidstate reaction.…”
Section: Introductionmentioning
confidence: 99%